Fire coal catalyst for combustion supporting and coking prevention of Zhundong coal as well as preparation and application of fire coal catalyst
By developing a dual-function catalyst containing components such as potassium nitrate, manganese nitrate, copper nitrate and other components, the problems of low combustion efficiency and coking in Zhundong Coal were solved, and the effects of efficient combustion and anti-coking were achieved.
Patent Information
- Application Number
- CN202411979183.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
During the combustion process, Jundong Coal is prone to low ignition points, incomplete combustion and severe coking, which affects combustion efficiency and increases maintenance costs. The existing coal-fired catalysts cannot effectively solve these problems.
Develop a dual-function catalyst to capture low-melting point sodium coal ash in coal through ingredients such as potassium nitrate, manganese nitrate, copper nitrate, etc., convert it into high-melting point ash, and promote combustion and increase the melting point of coal ash to prevent coking.
Significantly improve the combustion efficiency of Zhundong coal, achieve the coal-saving effect, and effectively prevent coking during the combustion process, increase the melting point of coal ash, and ensure the safe operation of equipment.
Smart Images

Figure BDA0005221127230000031 
Figure BDA0005221127230000041 
Figure BDA0005221127230000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coal combustion, and in particular to a dual-function catalyst with combustion-supporting and anti-coking properties for coal combustion in Zhundong area and a preparation method thereof. Background Art
[0002] In recent years, the proportion of coal in my country's energy consumption has continued to decline, but it still accounts for more than half, at 55.3%. The Zhundong region of Xinjiang has 390 billion tons of coal (called "Zhundong coal") resources, which is the largest integrated coalfield in my country. "Zhundong coal" is a high-alkali metal coal with high Na, K, Ca, etc., and has the characteristics of high volatility, low ash and low sulfur. In actual applications, Zhundong coal may encounter problems such as low ignition point and incomplete combustion during the combustion process, especially in large combustion equipment such as industrial boilers and power plants. It is easy to produce serious coking, which affects combustion efficiency and increases maintenance costs. In addition, coking can also cause problems such as burner blockage and reduced heat exchange efficiency, posing a threat to the safe operation of the equipment.
[0003] In order to improve these problems, it is particularly important to develop a coal-fired catalyst that can promote the efficient combustion of Zhundong coal and effectively prevent coking. Most of the existing coal-fired catalysts focus on improving combustion efficiency or reducing pollutant emissions. There are relatively few studies on preventing coking, and they are only for the combustion of ordinary coal. In view of the particularity of Zhundong coal, research reports on improving its combustion efficiency and preventing coking are even rarer. Therefore, it is necessary to develop a new type of combustion-supporting and anti-coking coal-fired catalyst to meet the needs of industrial applications. The decoking agents currently used on the market are mostly kaolin, corundum, quartz sand, Al2O3, and calcium oxide. Chinese patent CN 103627468 A discloses a coal-fired decoking agent, which uses aluminum compounds as the main agent and silicon compounds as the auxiliary agent in the raw material components, which can effectively slow down coking. Chinese patent CN108384597 A discloses a biomass circulating fluidized bed boiler anti-coking additive and its preparation method, the additive includes the following weight parts: coal gangue: 55-65%, Ca(OH)2: 30-40%, MnO2: 1-10%. These powder additives are used in large quantities, have high costs, and only have a decoking effect on ordinary coal. Chinese patent CN 116790302 A discloses a preparation method for a multifunctional liquid catalyst for coal boiler decoking, dust removal, coal saving, etc. The auxiliary agent used in the raw material component is a compound of a carbonate metal salt, a nitrate metal salt and a boric acid solution, which has a significant effect of improving the combustion efficiency of coal, and the coal saving rate is 3-5%, and has anti-coking, decoking and other effects. Although the acid has a good decoking effect, it will inevitably cause certain corrosion to the boiler equipment. Therefore, in view of the characteristics of Zhundong coal, it is of great significance to seek an economical, efficient and dual-functional coal-fired additive. Summary of the invention
[0004] The purpose of the present invention is to provide a coal-fired catalyst for supporting combustion of Zhundong coal and preventing coking and a preparation method thereof. The catalyst can not only significantly improve the combustion efficiency of Zhundong coal and achieve the effect of saving coal, but also increase the melting point of sodium in coal ash and effectively prevent coking during its combustion process.
[0005] Most of the above-mentioned prior arts are aimed at improving the combustion efficiency or anti-coking ability of ordinary coal. The powder additives are costly, and the liquid acidic additives will corrode boiler equipment, which is not suitable for large-scale application in industry. The present invention aims at the high Na, K, and Ca properties of Zhundong coal, and converts the coal ash Na, K, and Ca with high content and low melting point into high melting point compounds, so that they are fixed in the bottom ash. At the same time, the additive also has the effect of promoting combustion, thereby achieving the effect of saving coal and preventing coking.
[0006] Potassium nitrate, manganese nitrate, and copper nitrate can lower the ignition point of coal, nickel nitrate will accelerate the combustion of coal and its carbide, potassium nitrate, calcium chloride, and potassium dihydrogen phosphate will capture the low-melting-point sodium ash in the coal and convert it into high-melting-point ash, among which potassium, calcium, and other metals will form high-valent iron oxides with the iron element in the coal, raising the melting point of the ash, thereby achieving the dual effects of both promoting coal combustion and preventing coking. DETAILED DESCRIPTION
[0007] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0008] The application method of the combustion aid for Zhundong coal of the present invention is as follows: the mass ratio of Zhundong coal to coal-fired catalyst is 1:(0.0008-0.0012), the coal-fired catalyst is directly added in the process of coal blending, and after being stirred evenly, it is sent into a coal-fired boiler for combustion.
[0009] The ignition point of the coal sample without additives is 385℃, the burnout temperature is 500℃, and the temperature corresponding to the maximum burning rate is 420℃. The melting point of coal ash is 1108℃.
[0010] According to the TA and DTG curves, the ignition temperature point, burnout temperature point and temperature corresponding to the maximum burning rate of the sample are analyzed: Ignition temperature point: The intersection of the tangent line at the horizontal position before the TG step and the tangent line at the inflection point of the curve is the sample ignition point. Burnout temperature point: The intersection of the tangent line at the horizontal position after the TG step and the tangent line at the inflection point of the curve is the sample burnout point. The temperature point corresponding to the maximum burning rate: The temperature corresponding to the point with the largest change in mass rate on the DTG curve is the temperature point corresponding to the maximum burning rate.
[0011] Ash melting point test method: GB219-74.
[0012] The experimental process is as follows: take a 50mL beaker and weigh 10g of coal powder, add 20mL of tap water and stir evenly, let it stand overnight, set the oven temperature to 80℃ to dry the coal powder (7-8h). In order to ensure the uniformity of the sample, pour all the samples into a ziplock bag and mix them evenly. Take 100mg of the sample and grind it in a mortar, and take it out for testing. Thermogravimetric analysis conditions: starting temperature: 30℃; end temperature: 900℃; heating rate: 10℃ / min, air atmosphere, flow rate of 100mL / min, thermogravimetric analysis sample amount: 5.0000-10.0000mg. According to the TG and DTG curves, the ignition point, burnout temperature and the temperature corresponding to the maximum combustion rate are analyzed. The ash melting point is tested using an ash melting point tester, and the ash is prepared according to the provisions of GB 212-63 "Industrial Analysis Methods of Coal" for ashing treatment.
[0013] Embodiment 1:
[0014] Additive composition:
[0015]
[0016] The mass ratio of Zhundong coal to additives is 1:0.0008. The ignition point (367.5℃) is 17.5℃ lower than that of the original coal sample, the burnout temperature (478℃) is 22℃ lower than that of the original coal, and the temperature corresponding to the maximum combustion rate (408℃) is 12℃ lower than that of the original coal. The coal saving rate is about 4%; the mass fraction of potassium and calcium elements is about 23%, which can increase the melting point of coal ash (1203℃) by about 95℃.
[0017] The preparation of the coal-fired catalyst comprises the following steps:
[0018] a. Dissolve calcium chloride, potassium nitrate and copper nitrate in water (200 mL) to form a uniform solution;
[0019] b. Dissolve magnesium chloride, nickel nitrate, sodium nitrate, manganese nitrate, potassium dihydrogen phosphate, potassium aluminum sulfate, and basic copper carbonate in water (200 mL) and ethanol (50 mL) to form a uniform solution;
[0020] c. The solution obtained in step a was poured into the solution obtained in step b and heated to 70 ° C and stirred for 3 hours;
[0021] d. Add a dispersant (oleic acid: hydrogenated silicone oil in a mass ratio of 3:1) to step c, and ultrasonicate the mixed solution at 40°C for 1 hour.
[0022] Embodiment 2:
[0023] Additive composition:
[0024]
[0025] The mass ratio of Zhundong coal to additives is 1:0.001. The ignition point (374℃) is 11.0℃ lower than that of the original coal sample, the burnout temperature (482℃) is 18℃ lower than that of the original coal, and the temperature corresponding to the maximum combustion rate (412℃) is 5℃ lower than that of the original coal. The coal saving rate is about 3%; the mass fraction of potassium and calcium elements is about 22%, which can increase the melting point of coal ash (1173℃) by about 65℃.
[0026] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0027] Embodiment 3:
[0028] Additive composition:
[0029]
[0030] The mass ratio of Zhundong coal to additives is 1:0.0012, the mass fraction of copper nitrate, potassium nitrate and manganese nitrate is 17%, the ignition point (265℃) is 20℃ lower than that of the original coal sample, the burnout temperature (487℃) is 13℃ lower than that of the original coal, and the temperature corresponding to the maximum combustion rate (412℃) is 8℃ lower than that of the original coal, and the coal saving rate is about 4%; the mass fraction of potassium and calcium elements is about 22%, which can increase the melting point of coal ash (1178℃) by about 70℃.
[0031] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0032] Embodiment 4:
[0033] Additive composition:
[0034]
[0035] The mass ratio of Zhundong coal to additives is 1:0.001, the mass fraction of copper nitrate, potassium nitrate and manganese nitrate is 20%, the ignition point (370℃) is 15℃ lower than that of the original coal sample, the burnout temperature (490℃) is 10℃ lower than that of the original coal, and the temperature corresponding to the maximum combustion rate (415℃) is 5℃ lower than that of the original coal. The coal saving rate is about 4%, and the mass fraction of potassium and calcium elements is about 23%, which can increase the melting point of coal ash (1168℃) by about 60℃.
[0036] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0037] Embodiment 5:
[0038] Additive composition:
[0039]
[0040]
[0041] The mass ratio of Zhundong coal to additives is 1:0.001, the mass fraction of copper nitrate, potassium nitrate and manganese nitrate is 19%, the ignition point (372℃) is 13℃ lower than that of the original coal sample, the burnout temperature (485℃) is 15℃ lower than that of the original coal, and the temperature corresponding to the maximum combustion rate (419℃) is 1℃ lower than that of the original coal. The coal saving rate is about 2%, and the mass fraction of potassium and calcium elements is about 24%, which can increase the melting point of coal ash (1161℃) by about 53℃.
[0042] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0043] Embodiment 6:
[0044] Additive composition:
[0045]
[0046] The mass ratio of Zhundong coal to additives is 1:0.001, the mass fraction of copper nitrate, potassium nitrate and manganese nitrate is 19%, the ignition point (375℃) is 10℃ lower than that of the original coal sample, the burnout temperature (481℃) is 19℃ lower than that of the original coal, and the temperature corresponding to the maximum combustion rate (420℃) is unchanged compared with the original coal. The coal saving rate is about 2%, and the mass fraction of potassium and calcium elements is about 23%, which can increase the ash melting point (1150℃) by about 42℃.
[0047] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0048] Embodiment 7:
[0049] Additive composition:
[0050]
[0051] The mass ratio of Zhundong coal to additives is 1:0.001, the mass fraction of copper nitrate, potassium nitrate and manganese nitrate is 19%, the ignition point (366℃) is 19℃ lower than that of the original coal sample, the burnout temperature (479℃) is 21℃ lower than that of the original coal, and the temperature corresponding to the maximum combustion rate (411℃) is 9℃ lower than that of the original coal. The coal saving rate is about 3%, the mass fraction of potassium and calcium elements is about 27%, and the ash melting point (1161℃) can be increased by about 53℃.
[0052] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0053] Usage method: dilute the Zhundong coal-fired catalyst prepared by the present invention with water to 5 times of the original volume, and evenly spray it on the coal. The mass ratio of Zhundong coal to the coal-fired catalyst is 1: (0.0008-0.0012), which can significantly promote coal combustion, improve coal combustion efficiency, prevent coking during combustion, and the coal saving rate is between 2% and 5%.
[0054] Comparative Example 1:
[0055] Additive composition:
[0056]
[0057] The mass ratio of Zhundong coal to additives is 1:0.0012, the mass fraction of copper nitrate, potassium nitrate and manganese nitrate is 10%, the ignition point (383°C) is 2°C lower than that of the raw coal sample, the burnout temperature (500°C) remains unchanged with the raw coal, the temperature corresponding to the maximum combustion rate (420°C) remains unchanged with the raw coal, the coal saving rate is about 0%, the mass fraction of potassium and calcium elements is about 12%, and the ash melting point (1118°C) is increased by about 10°C. The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in the two steps ab is 1:1.
[0058] Comparative Example 2:
[0059] Additive composition:
[0060]
[0061] The mass ratio of Zhundong coal to additives is 1:0.001, and copper nitrate and potassium nitrate are replaced by copper sulfate and potassium chloride. The mass fraction of copper sulfate, potassium chloride, and manganese nitrate is 8%, and the ignition point (380℃) is only 5℃ lower than the original coal sample, and the burnout temperature (498℃) is 2℃ lower than the original coal. The temperature corresponding to the maximum combustion rate (420℃) remains unchanged compared with the original coal, and the coal saving rate is about 0%; the mass fraction of potassium is about 9%, which can increase the ash melting point (1158℃) by about 50℃.
[0062] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0063] Comparative Example 3:
[0064] Additive composition:
[0065]
[0066]
[0067] The mass ratio of Zhundong coal to additives is 1:0.001, and calcium chloride and potassium chloride are replaced by calcium hydroxide and potassium bromide. The mass fraction of copper nitrate, potassium bromide, and manganese nitrate is 20%, the ignition point (378℃) is only 7℃ lower than the original coal sample, the burnout temperature (495℃) is 5℃ lower than the original coal, the temperature corresponding to the maximum combustion rate (421℃) is 1℃ higher than the original coal, and the coal saving rate is about 0%; the mass fraction of potassium element is about 14%, which can increase the ash melting point (1149℃) by about 41℃.
[0068] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0069] Comparative Example 4:
[0070] Additive composition:
[0071]
[0072] The mass ratio of Zhundong coal to additives is 1:0.001, the mass fraction of copper nitrate and potassium nitrate is 13%, the ignition point (382°C) is only 3°C lower than that of the original coal sample, the burnout temperature (500°C) is unchanged compared with the original coal, the temperature corresponding to the maximum combustion rate (425°C) is 5°C higher than that of the original coal, and the coal saving rate is about 0%; the mass fraction of potassium element is about 20%, which can increase the ash melting point (1129°C) by about 11°C. The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, except that manganese nitrate is not added, which shows that manganese nitrate has a great effect on reducing the ignition point of coal.
[0073] The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, and the mass ratio of water used in steps ab is 1:1.
[0074] Comparative Example 5:
[0075] Additive composition:
[0076]
[0077] The mass ratio of Zhundong coal to additives is 1:0.0008, the mass fraction of manganese nitrate is 12%, the ignition point (382.5°C) is 2.5°C lower than that of the raw coal sample, the burnout temperature (492°C) is 8°C lower than that of the raw coal, the temperature corresponding to the maximum combustion rate (415°C) is 5°C lower than that of the raw coal, and the coal saving rate is about 1%; the mass fraction of potassium and calcium elements is about 17%, which can increase the ash melting point (1135°C) by about 27°C. The preparation process and conditions of the coal-fired catalyst are the same as those of the preparation of the coal-fired catalyst in Example 1, except that 12% manganese nitrate is added, and excessive manganese nitrate will hinder combustion, and the mass ratio of water used in the two steps ab is 1:1.
[0078] Comparative Example 6:
[0079] Additive composition:
[0080]
[0081] The mass ratio of Zhundong coal to additives is 1:0.0008, the mass fraction of copper nitrate, potassium nitrate and manganese nitrate is 22%, the ignition point (367℃) is 18℃ lower than that of the original coal sample, the burnout temperature (480℃) is 20℃ lower than that of the original coal, and the temperature corresponding to the maximum combustion rate (408℃) is 12℃ lower than that of the original coal, and the coal saving rate is about 3%; the mass fraction of calcium chloride is about 10%, and the ash melting point is 1120℃, which is increased by about 12℃.
[0082] The preparation process and conditions of the coal-fired catalyst are the same as those of Example 1, except that 10% calcium chloride is added, as excess calcium chloride will reduce the melting point of coal ash. The mass ratio of water used in steps ab is 1:1.
Claims
1. A coal-fired catalyst for combustion-supporting and coking-preventing Zhundong coal, characterized in that: The components and mass percentages are: 35-55% water, 5-10% ethanol, 3-8% calcium chloride, 5-10% potassium nitrate, 2-5% copper nitrate, 1-6% nickel nitrate, 5-10% sodium nitrate, 5-10% manganese nitrate, 4-8% potassium dihydrogen phosphate, 1-5% potassium aluminum sulfate, 1-4% basic copper carbonate, and 1-2% dispersant.
2. The coal fuel additive according to claim 1, characterized in that: Preferably, water is 30-45%, ethanol is 5-8%, calcium chloride is 5-8%, potassium nitrate is 8-10%, copper nitrate is 3-5%, nickel nitrate is 3-5%, sodium nitrate is 7-10%, manganese nitrate is 8-10%, potassium dihydrogen phosphate is 7-8%, potassium aluminum sulfate is 3-5%, basic copper carbonate is 2-4%, and dispersant is 1.5-2%.
3. The coal fuel additive according to claim 1 or 2, characterized in that: The dispersant is a combination of oleic acid and hydrogenated silicone oil in a mass ratio of 3-6:1 (preferably 3:1).
4. A method for preparing a combustion-supporting and coking-resistant coal-fired catalyst for Zhundong coal combustion according to claim 1, 2 or 3, characterized in that: The following steps are involved: a. Dissolve calcium chloride, potassium nitrate and copper nitrate in water (40%-60% of the total water required) to form a uniform solution; b. Dissolve magnesium chloride, nickel nitrate, sodium nitrate, manganese nitrate, potassium dihydrogen phosphate, potassium aluminum sulfate, and basic copper carbonate in water (40%-60% of the total water required) and ethanol to form a uniform solution; c. The solution obtained in step a is poured into the solution obtained in step b, and the mixture is heated to 50-80 ° C and stirred for 2-4 hours; d. Add a dispersant to step c, and ultrasonicate or stir the mixed solution at 40-60°C for 1-3 hours.
5. Use of the combustion-supporting and coking-preventing coal-fired catalyst according to claim 1, 2 or 3 in the process of catalyzing the combustion of Zhundong coal.
6. The use according to claim 5, characterized in that: The coal-fired catalyst or coal-fired catalyst water dilution (water: coal-fired catalyst mass ratio = 4-6:1) is added to coal for combustion, and the mass ratio of Zhundong coal to combustion aid is 1:(0.0008-0.0012), preferably 1:0.0009-0.0011.
Citation Information
Patent Citations
Novel decoking agent for fire coal
CN103627468A
Biomass circulating fluidized bed boiler anti-coking additive as well as preparation and use method thereof
CN108384597A
Preparation method of decoking, dust removing and coal saving catalyst for coal-fired boiler
CN116790302A